Sustainable development of traditional villages cultural landscape driven by red tourism: A case study of Wangping Village in Sichuan province - Cai Pengcheng; Ubong Imang (Scopus, 2024)
Red tourism is an important resource for the transformation and development of traditional villages in old revolutionary base areas, and it promotes the integration and reconstruction of the cultural landscape of traditional villages. Taking Wangping Village in Sichuan Province as an example, this paper adopts a mixed method research design combining qualitative and quantitative methods. By sorting out the logical correlation between sustainable development theory and the reconstruction of traditional village cultural landscape, this paper conducts an empirical study on the sustainable development model of Wangping Village cultural landscape and the impact perception of villagers. It was found that the cultural landscape of Wangping Village had been significantly reconstructed under the drive of red tourism. In Wangping Village, the resident's perception of the impact on the protection and development of the village cultural landscape is mainly positive, and they support the continuous promotion of the protection and development of the village cultural landscape. The empirical research on the sustainable development model of traditional village cultural landscape driven by red tourism and residents' impact perception aims to enrich the research on the theoretical system of sustainable development of traditional villages, which has certain theoretical value and practical significance for the protection and development of traditional villages.